Antagonism of 5‐HT7 Receptors as a Promising Target for Gastric Cancer via Apoptotic Pathway - Cinar, Irfan; Dincer, Busra; Cadirci, Elif; Kara, Salih; Yildirgan, Mehmet Ilhan; Halici, Zekai; Palabiyik‐Yucelik, Saziye Sezin (Wiley, 2025)
ABSTRACT Although current treatment strategies have improved clinical outcomes for gastric cancer, they present a challenging prognosis that necessitates novel therapeutic approaches. The 5‐HT7 receptor, a member of the serotonin receptor family, plays a significant role in influencing the pathogenesis of various cancer types. This study seeks to investigate the complex interactions among 5‐HT7 receptors, gastric cancer, and apoptotic processes. A comprehensive set of experimental techniques was employed, including in vitro staining assays for apoptosis assessment, real‐time PCR, and cell proliferation assays. The findings indicate that the 5‐HT7 receptor agonist enhances the proliferation of primary gastric tissue cancer cells and KATO‐III cells, whereas treatment with the 5‐HT7 receptor antagonist significantly inhibits cellular proliferation. Analysis of 5‐HT7 receptor mRNA expression in gastric cancer patient populations indicated significantly elevated levels in cancerous tissues when compared to those in healthy tissues. The administration of a 5‐HT7 receptor agonist (LP44) resulted in increased cell proliferation in primary gastric cancer cells and KATO‐III cell lines, whereas treatment with a 5‐HT7 receptor antagonist (SB‐269970) significantly inhibited proliferation. Additionally, KATO‐III cells treated with the 5‐HT7 receptor antagonist demonstrated a marked upregulation of caspase‐3, caspase‐9, and BAX gene mRNA levels. In contrast, treatment with the 5‐HT7 receptor antagonist was associated with a significant reduction in the expression of nuclear factor kappa B and 5‐HT7 receptor mRNA levels. Annexin V‐FITC/PI and Hoechst 33342 staining demonstrated a pronounced apoptotic effect through antagonism of 5‐HT7 receptors compared to other groups. Collectively, the findings of this study suggest that the enhanced expression of 5‐HT7 receptors influences gastric cancer formation by regulating the apoptotic axis. This provides a novel perspective for understanding the molecular mechanisms underlying the potential of 5‐HT7 receptors as a targeted approach for combating gastric cancer via the apoptotic pathway.
Keywords: Research Article